"We're just stuck in a daily routine": Implications of the temporal dimensions, demands and dispositions of mothering for leisure time physical activity. Issue 5 (17th May 2021) - Spotswood, Fiona; Nobles, James; Armstrong, Miranda
Abstract: The reduced physical activity of women when they become mothers is a public health priority. Existing studies show that mothers have little time for leisure, or time that is fragmented and requiring negotiation with others. However, the temporal features of mothering are undertheorised and qualitative studies tend to focus on how mothers can skilfully construct physically active identities and balance societal expectations about being a "good mother". In line with other research that focuses on the configuration of everyday practices that condition the "possibilities" for health‐related practices like physical activity, we shift our focus away from the resisting capacities of mothers to the temporal features of mothering practices. We interrogate the lived experiences of 15 mothers of preschool children in deprived urban areas and illuminate the inherent temporal dimensions, demands and dispositions of mothering practices that condition the possibility of leisure time physical activity being undertaken. Together, these temporal features mean mothering practices can readily work against leisure time physical activity. The focus on the mothering practices rather than mothers brings a novel perspective for developing public health policy designed to support mothers into regular leisure time physical activity.